2002
DOI: 10.1177/019263650208663007
|View full text |Cite
|
Sign up to set email alerts
|

Block Scheduling: Is It Cost-Effective?

Abstract: Many school districts that have adopted block scheduling are trying to determine if the change was worth the effort. This case study examined one school district's attempt to answer the question: Is block scheduling cost-effective? Analysis of a wide range of data suggests that traditional notions of cost-effectiveness are not always applicable when considering school reform. A novel interpretation of cost-effectiveness emerged that may encourage districts to make further improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…Duel (1999), using a nonequivalent, pretest-posttest design, concluded that block scheduling had no significant effect on standardized test or AP exam scores. Based on a chi-squared analysis and descriptive statistics, Lare et al (2002) reported that block scheduling had no significant effect on AP or ACT exam scores. In contrast to the impact on standardized test scores, Snyder (1997) concluded that AP scores dropped slightly after the implementation of a block schedule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Duel (1999), using a nonequivalent, pretest-posttest design, concluded that block scheduling had no significant effect on standardized test or AP exam scores. Based on a chi-squared analysis and descriptive statistics, Lare et al (2002) reported that block scheduling had no significant effect on AP or ACT exam scores. In contrast to the impact on standardized test scores, Snyder (1997) concluded that AP scores dropped slightly after the implementation of a block schedule.…”
Section: Resultsmentioning
confidence: 99%
“…The settings included Florida (Duel, 1999;Hamdy & Urich, 1998), Georgia (Payne & Jordan, 1996), Indiana (Snyder, 1997), Missouri (Limback, 1998;Stader, 2001), New Jersey (Evans et al, 2002), North Carolina (Queen et al, 1997), Tennessee (Fletcher, 1997), and Virginia (Pisapia & Westfall, 1997a, 1997b. Other studies offered only general geographic descriptions of the setting such as the Midwest (Weller & McLeskey, 2000), the Southwest (Knight et al, 1999) or the West (Lare et al, 2002).…”
Section: Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, traditional middle school and high school schedules are six to seven periods per day with each period lasting between 45 and 55 min. From an organizational standpoint, this format is the most efficient design as it allows for the easy arrangement of courses, advisories, teacher planning periods, and other school-wide courses and requires fewer teachers than block or flexible schedules [69]. However, the traditional schedule format is rigid.…”
Section: Structures Of Timementioning
confidence: 99%
“…Linking scheduling formats to student achievement is very complex as so many factors interact with student learning, including teacher content knowledge and pedagogy [66,74]. Additionally, few studies exist on the ways in which scheduling formats are developmentally responsive to the academic learning needs of young adolescents (e.g., [69,75,76]).…”
Section: Structures Of Timementioning
confidence: 99%